[Plaque] at the entrance to the B.H.A.S. offices, 55 Collins Street, Melbourne, Victoria, architect: H. & F. Norris, 1979 - Sievers, Wolfgang, 1913-2007. (1979)
Text on plaque: "William Shepperson, Brian Bays, Church Wardens, 1723".
Condition: Good.
Title devised by cataloguer based on inscription on paper sleeve.
Part of the collection: Wolfgang Sievers photographic archive.
Sievers number: EC4623EA.
Also available online
Keywords: Norris Architects; Broken Hill Associated Smelters -- Buildings -- Photographs; Office buildings -- Victoria -- Melbourne -- Photographs; Interior decoration -- Victoria -- Melbourne -- Photographs